Time and events: on the phenomenology of temporal experience in schizophrenia : (ancillary article to EAWE Domain 2) - Fuchs, Thomas; Van Duppen, Zeno (Psychopathology, 2017)
Temporality and its disturbances have been a major topic of phenomenological psychopathology. Particularly Minkowski, Kimura, and Blankenburg described the temporal dimension of schizophrenia. After a brief introduction to their ideas, we describe more recent approaches to temporality in more depth. To this aim, we first distinguish between implicit and explicit time. Implicit time is based on the constitutive synthesis of inner time consciousness on the one hand, and on the conative-affective dynamics of life on the other. Explicit or conscious time experience arises with an interruption or negation of implicit time, and it unfolds itself in the dimensions of present, past, and future. Implicit time is based on a fluid and tacit bodily functioning and on affective synchronization with others, while explicit time arises through states of desynchronization, for example through retardation or acceleration of subjective time in relation to the social sphere. We clarify how a disturbance in temporality can lead to major symptoms of schizophrenia, such as thought disorders, hallucinations, or passivity experiences, and then consider the role of explicit temporal disturbances in schizophrenia.
Gesehen am 01.06.2018